The Effect of 20-20-20 Rule Dissemination and Artificial Tears Administration in High School Students Diagnosed with Computer Vision Syndrome - Bambang Subakti Zulkarnain; Aniek Setiya Budiatin; Toetik Aryani; Rozalina Loebis (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2021)
Computers and gadgets are modern tools for assisting Senior High School students’ work. However, using gadgets more than 2 hours a day may cause computer vision syndrome (CVS), which can interfere with academic activities. CVS main symptom is dry eyes. CVS could be prevented by applying the 20-20-20 rule and artificial tears. A total of 100 students from two public high schools in Kediri with 50 students from each school were selected for this community service. All students diagnosed with CVS participated in the dissemination of 20-20-20 rule and artificial tear administration. The pre-test and post-test scores, the Tear Break Up Time Test (TBUT) and the Ocular Disease Surface Index (OSDI) were measured within two weeks. TBUT and OSDI are parameters for measuring dry eye. Likewise, interviews were conducted to assess the adherence to the 20-20-20 rule and artificial tea administration. The results showed the knowledge level increased (p <0.0001). Most students understood 20-20-20 rule and how to administer artificial tears correctly. However, the adherence to both methods was approximately 50%. There was an improvement in the TBUT (p <0.0001) for dry eyes but not for OSDI (p> 0.05). Applying the 20-20-20 rule and artificial tears could be used for CVS treatment.